Identifying Gaps in Community Pharmacists’ Competence in Medication Risk Management in Routine Dispensing - Kallio, Sonja (Innov Pharm, 2021)
BACKGROUND: Community pharmacists increasingly contribute to medication risk management while dispensing medicines to outpatients. Their risk management actions are shifting from medication counselling towards reviewing medications and following-up their therapeutic effects and outcomes. Acquiring these more clinical tasks require more patient care-oriented competences. OBJECTIVE: To identify gaps in community pharmacists’ competence in medication risk management in routine dispensing. SETTING: All community pharmacies in Finland. METHOD: A national cross-sectional online survey was conducted through the Association of Finnish Pharmacies (n=574 community pharmacies) and the university pharmacies (n=2) in 2015. One pharmacist from each pharmacy was recommended to report on behalf of their outlet. MAIN OUTCOME MEASURE: Community pharmacists’ self-assessed competence to: 1) identify medication-related risks, 2) utilise electronic tools in medication risk management, and 3) identify their perceived needs for developing competence in medication risk management. RESULTS: Responses were received from 169 community pharmacies (response rate 29%). The highest proportion of good competency estimates were self-assessed in confirming doses (98% of the respondents evaluated their competence to be good) and identifying drug-drug interactions (83%). Competence to identify adverse effects, such as serotonergic load (10%) and anticholinergic load (12%), was most seldomly perceived as good. Of the wide range of electronic databases available, respondents most commonly reported using daily summaries of product characteristics (97% of the respondents), the checklist-type generic medicines information database that supports in medication counselling (85%), and the programme assisting in identifying drug-drug interactions (83%). The most commonly reported training needs were related to the identification of serotonergic load (63%), anticholinergic load (62%), and evaluating the clinical significance of drug-drug interactions (54%). CONCLUSION: The results indicate remarkable gaps in community pharmacists’ current competence in medication risk management, particularly in their competence in applied and geriatric pharmacotherapy.